Théorème du point fixe de Banach - BRAHIMI, Halima; SOBTI, Naouel; SENIGRA, Fatma (university of eloued جامعة الوادي, 2014)
قمنا في هذا العمل بتقديم نظرية النقطة الصامدة لبناخ مع الاشارة الى أهمية برهانها المتمثل في التقريبات المتتالية. و في الاخير قدمنا نماذج مختلفة حول تطبيقاتها فيما يخص التحليل الرياضي، العددي و الجبري.In this work , we have proposed the Banach fixed point theorem, with reference to the importance of their demonstration which is successive approximation , finally we have consider different models of fixed point applications in mathematical analysis material, numerical and algebraic.
mémoire licence matimatuque
Keywords: فضاء متري, متتالية كوشي, فضاء بناخ, التطبيق المقلص, النقطة الصامدة, التقريبات المتتالية.; metric space, sequence Cauchy, Banach space, contracting application, fixed point, successive approximation.